2018
DOI: 10.3390/lubricants6040105
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Investigations on Transient Run-Up Procedures of Journal Bearings Including Mixed Friction Conditions

Abstract: This paper focuses on the operating behavior of journal bearings for industrial machinery application during run-ups. For this purpose, a numerical simulation code that is based on a two-dimensional extended and generalized Reynolds equation and a full three-dimensional energy equation, was advanced by a theoretical model considering the effects of mixed friction and warming of journal components during start-up. The mixed friction routine contained the elastic half-spaces model proposed by Boussinesq, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…An application of the theory of Greenwood and Williamson [24] provides a relation between the mean film thickness on the node of the numerical grid and solid contact pressure due to the interaction of the asperities that is shown in Figure 7b. The contact surface features a root mean square roughness value of Rq = 2.83 μm and matches the one earlier presented by the authors in [25]. A turning process generates the surface topography that features small grooves in the circumferential direction.…”
Section: Flow Factors and Solid Contact Pressuresupporting
confidence: 85%
“…An application of the theory of Greenwood and Williamson [24] provides a relation between the mean film thickness on the node of the numerical grid and solid contact pressure due to the interaction of the asperities that is shown in Figure 7b. The contact surface features a root mean square roughness value of Rq = 2.83 μm and matches the one earlier presented by the authors in [25]. A turning process generates the surface topography that features small grooves in the circumferential direction.…”
Section: Flow Factors and Solid Contact Pressuresupporting
confidence: 85%
“…From Figures 13 and 16, it is also observed that the whirl ratio and mass parameters are insensitive to uncertainty in oil viscosity and supply pressure for some specific operating conditions (ε = 0.6-0.7 for the whirl ratio and ε = 0.4-0.6 for the mass parameter) indicating robust operating conditions. Figures 6,9,12,15,and 18 show the effect of oil viscosity and supply pressure on the hydrodynamic performance of a two-axial-groove journal bearing for various degrees of stochasticity. From where it can be observed that the effect of stochasticity in oil viscosity and supply pressure increases as the degree of stochasticity increases.…”
Section: Resultsmentioning
confidence: 99%
“…The existing design methodology of a journal bearing is completely based on the theoretical results obtained from the deterministic analysis without considering the geometrical and operational uncertainties. As a result, a significant difference 12 between the experimental and theoretical results is observed. In this context, the inclusion of uncertainties in geometric parameters or operating conditions in the design process of journal bearings is an important design issue.…”
Section: Introductionmentioning
confidence: 92%
“…The combination of physical and virtual simulation, and thus experimental and computational results, shows high potential for increasing our basic understanding of tribosystems [26,27]. Therefore, this combination can be used for the optimization of critical journal bearing systems, for example, the crankshaft bearings of automotive combustion engines.…”
Section: Introductionmentioning
confidence: 99%